2006
DOI: 10.1001/archpedi.160.7.674
|View full text |Cite
|
Sign up to set email alerts
|

Use of Human Immunodeficiency Virus Postexposure Prophylaxis in Adolescent Sexual Assault Victims

Abstract: We observed low rates of PEP completion among adolescent sexual assault survivors. Potential difficulties of using PEP in this population include uncertainties regarding exposure, high rates of psychiatric comorbidity, and low rates of return for follow-up care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
1
26
0
2
Order By: Relevance
“…85 A retrospective study found that uncertainties regarding exposure, high rates of psychiatric comorbidity, and low rates of return for follow-up care were all factors in the low rates of adherence to postexposure prophylaxis. 86 Centers that specialize in treatment of sexual assault victims often provide care without cost to their clients and can advise about local resources when payment, confidentiality, and safety are concerns. No large studies examining different combinations of treatment have been performed with sexual assault victims, but on the basis of current occupational-exposure guidelines, 2 nucleoside reverse-transcriptase inhibitors and 1 of either a nonnucleoside reverse-transcriptase inhibitor or protease inhibitor for 4 weeks is recommended.…”
Section: Acute Carementioning
confidence: 99%
“…85 A retrospective study found that uncertainties regarding exposure, high rates of psychiatric comorbidity, and low rates of return for follow-up care were all factors in the low rates of adherence to postexposure prophylaxis. 86 Centers that specialize in treatment of sexual assault victims often provide care without cost to their clients and can advise about local resources when payment, confidentiality, and safety are concerns. No large studies examining different combinations of treatment have been performed with sexual assault victims, but on the basis of current occupational-exposure guidelines, 2 nucleoside reverse-transcriptase inhibitors and 1 of either a nonnucleoside reverse-transcriptase inhibitor or protease inhibitor for 4 weeks is recommended.…”
Section: Acute Carementioning
confidence: 99%
“…[2][3][4][5][6][7] However, U.S. ED clinicians report giving HIV PEP much more often to health care workers (HCWs) than non-HCWs, even when the risks of infection are similar. 2 Studies also indicate that HIV PEP, occupational and nonoccupational, has been prescribed in U.S. EDs when it should not have been and was not offered when it could have been.…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with patient nPEP acceptance were similar to those associated with provider offering of nPEP (see Table 8). Again, the factor most frequently found was a positive association with high-risk exposure and/or a HIV-positive assailant Loutfy et al, 2008;Myles et al, 2000;Olshen et al, 2006;Wiebe et al, 2000). Lack of insurance or financial hardship was negatively associated with acceptance (Myles et al, 2000;Wiebe et al, 2000).…”
Section: Npep Acceptancementioning
confidence: 99%